Relationships between tourists and intelligent virtual assistants: Promoting the love ties - Loureiro, S. M. C.; Bilro, R. G.; Japutra, A.; Molinillo, S. (AIRSI2020 Conference Proceedings, 2020)
The present working paper intends to explore how tourists and intelligent virtual assistants may relate to each other in order to create love ties. The following research objectives will be pursued: (i) exploring attachment and perceived value as antecedents of love toward the intelligent virtual assistants, (ii) understanding loyalty intentions as outcomes of love toward the intelligent virtual assistants.